THE INFLUENCE OF CREDIT RISK, LIQUIDITY, AND COST OF FUNDS ON PROFITABILITY PERFORMANCE (A STUDY AT PT BANK TABUNGAN NEGARA (PERSERO) Tbk) - Rani Rachmawati; Sri Sutrismi (Universitas Tulungagung, 2026)
Bank profitability in Indonesia has been shaped by considerable volatility in credit risk, liquidity, and funding costs across the pre-pandemic, pandemic, and post-tightening periods between 2015 and 2025. This study aims to analyze the effect of credit risk, liquidity, and cost of funds on the financial performance of PT Bank Tabungan Negara (Persero) Tbk over the 2015–2025 period, both partially and simultaneously. The study draws on 44 quarterly observations derived from Bank BTN's published, audited financial and annual reports, and the relationships among constructs are estimated using Partial Least Squares–Structural Equation Modeling (PLS-SEM) processed through SmartPLS. The results show that credit risk has a significant negative effect on financial performance, while liquidity and cost of funds have no significant effect. The coefficient of determination indicates that the three variables jointly account for only a limited proportion of the variation in financial performance, so their simultaneous influence should be interpreted as modest rather than dominant, with most of the variation attributable to factors outside the model. These findings suggest that credit risk governance should be prioritised as the primary lever for sustaining bank profitability, offering practical guidance for bank management and for the Otoritas Jasa Keuangan in strengthening asset-quality-focused supervisory frameworks.